Homeowners' and architects' perspectives on wood and wood products as preferred material for building construction in Malaysia - Ab Latib, Hazirah (2020)
The Malaysian construction industry is one of the driving forces of the country’s economy. The construction sector accounted for 10.1% of the country’s Gross Domestic Product (GDP) in 2018. However, the consumption of wood and wood products in the construction sector accounted for only 18% of the total materials cost incurred by the construction sector in 2018. Therefore, it is important to determine the main reasons that deter homeowners and architects from using wood and wood products in the buildings. In this respect, the objective of this study was to determine the preferences of homeowners and architects for wood and wood products for specific applications in buildings, and to assess the attributes that influenced its utilization in building construction. The study was conducted through a questionnaire survey of 137 practicing architects throughout Malaysia, with a matching number of 137 homeowners. The response rate for the questionnaire survey was 31% or 43 respondents from each category. The application of wood and wood products by architects was focused primarily on non-structural applications rather than structural applications. It was found that cost, customer demand, durability, natural beauty, availability, ease of design, and workability were primary considerations for architects in specifying wood and wood products in building construction. A factor analysis of the results showed that building regulations, material quality and beauty, customer demand, and design and assembly were the primary determinants that influence architects specifying and using wood and wood products in building construction. It was apparent that the use of wood and wood products in building construction in Malaysia has the potential to be further increased through advertising and marketing in the material among the general public, as well as architects and specifiers. Generally, homeowners and architects were sensitive to the cost of construction which predetermined their preference for using wood and wood products. Other factors that were taken into consideration in specifying wood and wood products for building construction include durability, fire resistance and environmental friendliness. The study also showed that in order to increase the use of wood and wood products in building construction in Malaysia, the local councils should consider enforcing a minimum quantity of wood and wood products to be used in the building, before approval is given.